Differenze nel ciclo sessuale di popolazioni conviventi di Axinella damicornis (Esper.) ed Axinella verrucosa O. S. (Demospongiae) - Siribelli, L. (Bolletino di Zoologia, 1962)
The A. studies the period of sexual maturity of two related species of Demospongiae (Axinelia damicornis and Axinella verrucosa), an abundant material from two populations living in the same topographic area (rocky zone of the Secca della Gaiola in the bay of Naples). The A. has found that, the sexual cycles being out of phase by about 4 months, the two species reproductively isolated.